STUDY OF HEAVY METAL LEAD (PB) CONTENT IN THE CORAL REEF ENVIRONMENT OF PANJANG ISLAND, BANTEN - Fauzan, Ahmad Al; Utami, Dwi Amanda; Rachmayani, Rima; Nurhidayati, Ayu Utami (Marine Geological Institute of Indonesia, 2024)
Rapid industrial expansion in Banten has triggered a surge in pollution, impacting areas like Panjang Island in Banten Bay. Pollution on Panjang Island stems primarily from industrial operations and shipping activities. This study investigates the distribution of lead (Pb) metal concentrations in Panjang Island's coral reef environment, focusing on sediment and surface water. It also examines how seasonal variations, influenced by ocean currents, affect Pb concentration distribution. Data were gathered using purposive sampling, collecting sediment samples, surface water samples, and oceanographic data. Pb levels in both sediments and surface water underwent analysis at the National Research and Innovation Agency (BRIN) laboratory, employing atomic absorption spectrophotometry (AAS). Our findings indicate that during the transitional II season, Pb concentrations in sediment ranged from 4.2 to 17 mg/kg, while the westerly season showed Pb concentrations spanning 3.8 to 23.4 mg/kg. Surface water during these seasons exhibited Pb concentrations varying from 0 to 0.03 mg/l. Notably, at several monitoring stations, surface water Pb concentrations exceeded the threshold set by Regulation No. 22 of 2021, suggesting potential harm to the coral reef ecosystem surrounding Panjang Island. Elevated Pb concentrations were observed during the transitional II season in the island's western part and the westerly season in the eastern part. These disparities appear to be influenced by the direction of ocean currents, highlighting their role in shaping Pb distribution in Panjang Island's waters.